Synthesis of amphiphilic sulfonamide halogenated porphyrins: MALDI-TOFMS characterization and evaluation of 1-octanol/water partition coefficients - Monteiro, Carlos J. P. (2008)
Porphyrins are key precursors for development of photosensitizers for photodynamic therapy. A new series of ortho-halogenated tetraarylporphyrins with sulfonamide substituents have been synthesized via chlorosulfonation reaction and characterized by MALDI-TOFMS. To predict their partition properties, log KOW of a selected range of the synthesized halogenated amphiphilic porphyrins is described. A significant effect of the number and type of halogen group as well as on the number of sulfonamide side chain was observed. The determined 1-octanol/water partition coefficients showed that it is possible to obtain compounds with a wide range of lipophilicities, from log KOW=-2.71 till log KOW>4, which are suitable to optimize the biological efficacy of this class of sensitizers.